2008
DOI: 10.1016/j.jorganchem.2008.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of para-OH functionalized ECE-metalated pincer complexes

Abstract: a b s t r a c tVarious para-OH functionalized ECE-pincer metal complexes [MX(ECE-OH)L n ] (ECE-OH = [C 6 H 2 (CH 2 E) 2 -2,6-OH-4] À , E = NMe 2 , PPh 2 and SPh) were synthesized. The X-ray crystal structures of neutral [PdCl(SCS-OH)], [PdCl(NCN-OH)], and cationic [Pd(PCP-OH)(MeCN)](BF 4 ) are reported. The neutral halide complexes exhibit self-assembly to form polymeric chains via H-bonding involving the para-OH group as donors and the halide ligand on the metal as acceptors. Moreover, the halide ligand can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 93 publications
1
15
0
Order By: Relevance
“…For the PCP-pincer Pd complexes, no insertion was observed, but replacement of the halide by a h 1 -coordinated isocyanide generated the cationic, catalytically active species. Finally, this study showed that there is no need to generate a cationic palladium(II) species by prior treatment of the neutral species with, for example, Ag reagents (note that Ag halide salts are catalysts themselves) [22] for the ECE-pincer palladium species to catalyze the reaction of Eq. (1).…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…For the PCP-pincer Pd complexes, no insertion was observed, but replacement of the halide by a h 1 -coordinated isocyanide generated the cationic, catalytically active species. Finally, this study showed that there is no need to generate a cationic palladium(II) species by prior treatment of the neutral species with, for example, Ag reagents (note that Ag halide salts are catalysts themselves) [22] for the ECE-pincer palladium species to catalyze the reaction of Eq. (1).…”
Section: Introductionmentioning
confidence: 93%
“…[23] These complexes comprise both a trialkoxysilane and an organometallic fragment covalently connected through a carbamate linker. The presence of a long, non-polar tail increases the solubility of these complexes considerably.…”
Section: Immobilization Of Pcp-and Scs-pincer Palladium Complexes On mentioning
confidence: 99%
See 2 more Smart Citations
“…Interesting cases of non-covalent hydrogen bonding were discovered to occur between hydrogen donor atoms present in the para-substituent Z of MX {C 6 H 2 (CH 2 NMe 2 ) 2 -2,6-Z-4} on the one end and the hydrogen accepting site X of the metal-X grouping. For example, both in the solid state and in solution MCl{C 6 H 2 (CH 2 NMe 2 ) 2 -2,6-Z-4}, M ¼ Pt, Z ¼ OH [51], forms polymers via intermolecular OH/Cl H-bonding. However, when more conformational flexibility is present in Z, as is the case for M ¼ Pd, Z ¼ CH 2 OH, a dimeric structure is formed through mutual head-to-tail OH/Cl H-bonding.…”
Section: Reversible Binding Of So 2 In Crystalline Ptclmentioning
confidence: 99%